Assessing the Regulatory Functions of LncRNA SNHG11 in Gastric Cancer Cell Proliferation and Migration - Zhao, Danyi; Chen, Huawei; Wang, Bing (Frontiers in Cell and Developmental Biology, 2021)
The aim of this study was to assess the regulatory functions of SNHG11 in gastric cancer (GC) cell proliferation and migration. Dual-luciferase reporter assay and bioinformatics prediction [starBase (http://starbase.sysu.edu.cn/) and TargetScan (http://www.targetscan.org)] indicated that SNHG11 functions as a miR-184 sponge that can directly act on CDC25A. Compared with normal healthy gastric tissue and mucosal epithelial cell GES-1, SNHG11 and CDC25A expressions were dramatically increased in GC samples and cell lines, whereas microRNA-184 (miR-184) levels were reduced. SNHG11 silencing led to increased miR-184 and reduced CDC25A, whereas miR-184 downregulation recovered the expression of CDC25A. Additionally, miR-184 upregulation also played a role in regulating CDC25A ablation. Then, SNHG11 was silenced or miR-184 was upregulated in two GC cells (SGC-7901 and MKN-28). SNHG11 silencing and miR-184 upregulation caused a notable decrease in GC cell growth and proliferation and increased the apoptotic level of GC cells. Furthermore, SNHG11 silencing and miR-184 upregulation contributed to a decreased migration capacity of GC cells. Downregulated miR-184 expression in SNHG11 silenced GC cells showed that miR-184 inhibition reversed the effect of SNHG11 silencing on the growth, proliferation, apoptosis, and migration of GC cells. Moreover, in vivo xenograft experiments demonstrated that SNHG11 knockdown can inhibit tumor growth. These observations confirmed that SNHG11 acts as an oncogene, whereas miR-194 served as a tumor suppressor in GC development. SNHG11 may provide a new biomarker for GC diagnosis, treatment, and prognosis.